Comprehensive Evaluation of Decellularized Dental Pulp as a New Biomaterial for Regeneration of the Pulp-Dentin Complex - K. I. Melkonian; T. V. Rusinova; E. S. Zaporozhskaya-Abramova; E. A. Solop; I. I. Kartashevskiy; S. A. Knyshova; O. N. Risovannaya (Инновационная медицина Кубани)
Objective: To develop a detergent-enzymatic method and evaluate the quality of a decellularized pulp scaffold for regenerative endodontics.Materials and methods: Biomaterial and mesenchymal stem cells (MSCs) were derived from dental pulp that was obtained following third molar extraction indicated for orthodontic reasons in patients aged 14-18 years. The detergent-enzymatic method enabled to obtain a decellularized scaffold from pulp samples. The proliferative activity and viability of dental pulp-derived MSCs were assessed using trypan blue staining and XTT assay. To assess tissue response, Wistar rats underwent subcutaneous implantation of native and decellularized dental pulp. Explanted samples were stained with hematoxylin-eosin on days 7 and 14.Results: The detergent-enzymatic treatment of the dental pulp demonstrated the absence of nuclear material, whereas the histoarchitecture of the dental pulp was disturbed. The DNA content in the sample of the decellularized scaffold was 22.79 ± 2.1 ng/mg of tissue; the amount of DNA in the native sample was 78.5 ± 5.4 ng/mg of tissue. According to XTT assay results, no cytotoxicity of the decellularized scaffold against MSCs was found. Biopsy specimens of the rats with implanted decellularized dental pulp were characterized by no signs of inflammation.Conclusions: The study results will enable to create a biomaterial that can be the base of a tissue-engineered structure of the dental pulp and be used for the regeneration of the pulp-dentin complex.